2019
DOI: 10.1002/arch.21648
|View full text |Cite
|
Sign up to set email alerts
|

A novel hexamerin with an unexpected contribution to the prophenoloxidase activation system of the Chinese oak silkworm, Antheraea pernyi

Abstract: Hexamerin was originally identified as a storage protein but later confirmed to be involved in many physiological processes. In the present study, we cloned and characterized a novel hexamerin complementary DNA sequence from the Chinese oak silkworm, Antheraea pernyi (Ap‐hexamerin), which shows high homology with reported insect methionine‐rich hexamerins. The tissue distribution and time course of expression demonstrated that Ap‐hexamerin was predominantly synthesized in the fat body and the expression level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This nonclassical polyadenylation signal was also detected in Liriomyza sativa ( Huang et al 2009 , Chang et al 2019 ). Four putative hexamerin proteins contained the hexamerin family conserved domains hemocyanin N, hemocyanin M, and hemocyanin C, as in other insects ( Martins et al 2010 , Liu et al 2019 ). Hex 70a and Hex 70c belong to the class of aromatic amino acid-rich proteins that contain a relatively high quantity of aromatic amino acids (phenylalanine, tryptophan, and tyrosine > 15%).…”
Section: Discussionmentioning
confidence: 90%
“…This nonclassical polyadenylation signal was also detected in Liriomyza sativa ( Huang et al 2009 , Chang et al 2019 ). Four putative hexamerin proteins contained the hexamerin family conserved domains hemocyanin N, hemocyanin M, and hemocyanin C, as in other insects ( Martins et al 2010 , Liu et al 2019 ). Hex 70a and Hex 70c belong to the class of aromatic amino acid-rich proteins that contain a relatively high quantity of aromatic amino acids (phenylalanine, tryptophan, and tyrosine > 15%).…”
Section: Discussionmentioning
confidence: 90%
“…Neverthelesss, in addition to providing amino acids and energy, hexamerins participate in many other physiological processes, including transport of ecdysteroids and juvenile hormone (JH) (Braun & Wyatt, 1996), upregulation of prophenoloxidase activation (Liu et al. , 2020), caste regulation (Zhou et al. , 2006), diapause (Spiliotopoulos et al.…”
Section: Introductionmentioning
confidence: 99%
“…The functions that hexamerins are mostly associated with are molting, metamorphosis, and reproduction (Haunerland, 1996;Pan & Telfer, 1996;Wheeler et al, 2000;Pan & Telfer, 2001;Hahn & Wheeler, 2003;Manohar et al, 2010;Xie & Luan, 2014). Neverthelesss, in addition to providing amino acids and energy, hexamerins participate in many other physiological processes, including transport of ecdysteroids and juvenile hormone (JH) (Braun & Wyatt, 1996), upregulation of prophenoloxidase activation (Liu et al, 2020), caste regulation (Zhou et al, 2006), diapause (Spiliotopoulos et al, 2007), and even immune responses (Li et al, 2020). In cockroaches, allergen can cause allergic responses in humans and has been identified as a strong risk factors for the development of asthma (Do et al, 2016), but a large number of allergens identified from plants are storage proteins (Mills & Tatham, 2003).…”
Section: Introductionmentioning
confidence: 99%